(untitled) (Damascus University Journal of agriculture sciences, 2022)
Studies on the life table parameters of the cigarette beetle, Lasioderma serricorne (F.) (Coleoptera: Anobiidae) reared on chicken stock powder (maggi), Baker’s yeast, grains milo, dried ficus, and dried tobacco leaves, were carried out under laboratory conditions of 28±1°C, 65±5% RH and 16:8 h (day: night), the total reproduction rate (GRR) by females feeding on chicken stock powder (maggi), Baker’s yeast, grains milo, dried ficus, and dried tobacco leaves, was 47.46, 42.125, 31.75, 32.625 and 6.00 females/ females/generation, the net reproduction rate (R0) 47.46, 42.125, 31.75, 32.625 and 6.00 female/ female/day, respectively. The doubling time of population (DT) was 7.22, 6.30, 7.88, 7.97 and 25.67 days; intrinsic rate of increase (rm) was 0.096, 0.11, 0.088, 0.087 and 0.027 female/ female/day, respectively. This age-specific fecundity schedules reflect L.serricorne ability for doubling its population faster on Baker’s yeast than on (powdered chicken stock (Maggi), grains milo, dried ficus and dried tobacco leaves at the same temperature 28°± 1C.